Applicability Study of Air Side Heat Transfer Model of Fin-tube Heat Exchanger in Low Ambient Pressure - Zhang Jiawen; Liu Jianhua; Zhang Liang; Liu Qi (Zhileng xuebao)
The applicability of popular air-side heat transfer models of a flat fin-tube heat exchanger with high prediction accuracy are summarized in this paper. Their performance in a low ambient pressure (40–100 kPa) is analyzed under typical air conditioning conditions (air dry bulb temperature 27 oC, wet bulb temperature 19.5 oC, approach velocity 1?–4 m/s, inlet cooling water temperature 7–13 oC, and water flow rate 1.8 m/s). To check the applicability of these models, three heat exchangers with different tube rows (2/3/4) were tested. Experimental results showed that the data with large deviation appeared in the cases with a low ambient air pressure and the deviation could be +127.4%-–-36.6%. The predictions with models under atmospheric pressure were generally greater than the test results as the influence of atmospheric pressure on the Re number of the air side heat transfer was not considered. The effect of the number of tubes under a low-pressure environment on the heat transfer remains there and is more apparent. A correction term of ambient pressure was proposed based on the experimental data in this study. There was a substantial improvement of these three models’ prediction accuracy after this correction as follows: under the experimental conditions, the maximum deviation dropped to 32.63%, 24.91%, and 21.74% respectively; the average deviation was 1.79%, -2.90%, and -8.59% respectively; and the error range of ±20% covered 90.97%, 93.75%, and 88.96% respectively of the experimental values. Furthermore, pressure correction makes the models applicable to a more extensive range of ambient pressures.